2004
DOI: 10.1016/j.clinph.2003.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Familiar-face recognition and comparison: source analysis of scalp-recorded event-related potentials

Abstract: Objective: We studied the event-related potentials elicited by categorical matching of faces. The purpose was to find cortical sources responsible for face recognition and comparison.Methods: Nineteen healthy volunteers participated in the study. Each trial began with one of the two cues (S1) followed by consecutive pictures (S2 and S3). Each picture was a photograph of a familiar face with a superimposed abstract dot pattern. One cue directed attention to compare faces and another to compare patterns. 128-cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
22
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 25 publications
8
22
0
5
Order By: Relevance
“…It is possible that different generators contribute to the N170 component, depending on the task demands. Significant sources found in our study are consistent with generators described by a variety of previous studies (Sadeh, Podlipsky, Zhdanov, & Yovel, 2010;Herrmann, Ehlis, Muehlberger, & Fallgatter, 2005;Itier & Taylor, 2004;Mnatsakanian & Tarkka, 2004;Rossion et al, 2003;Bentin et al, 1996). Moreover, our results are also consistent with brain activations found in different functional brain imaging and intracortical recording studies of face perception.…”
Section: Discussionsupporting
confidence: 81%
“…It is possible that different generators contribute to the N170 component, depending on the task demands. Significant sources found in our study are consistent with generators described by a variety of previous studies (Sadeh, Podlipsky, Zhdanov, & Yovel, 2010;Herrmann, Ehlis, Muehlberger, & Fallgatter, 2005;Itier & Taylor, 2004;Mnatsakanian & Tarkka, 2004;Rossion et al, 2003;Bentin et al, 1996). Moreover, our results are also consistent with brain activations found in different functional brain imaging and intracortical recording studies of face perception.…”
Section: Discussionsupporting
confidence: 81%
“…For example, activities in the primary visual areas are evoked by the change in luminance, regardless of the stimulus shape. (2) The generator source of N170 has not yet been confirmed, although some regions such as the superior temporal sulcus (STS), inferior temporal (IT) area, and other surrounding regions are candidates, as reported in previous studies (Bötzel et al 1995;Herrmann et al 2005;Itier and Taylor 2004c;Mnatsakanian and Tarkka 2004;Pizzagalli et al 2002;Rossion et al 2003;Schweinberger et al 2002;Shibata et al 2002;Taylor et al 2001;Watanabe et al 2003); however, N170 could be contaminated with activity generated in the primary visual cortex, as described above. The source of M170 in previous MEG studies is considered to be only the IT area, since only the tangential dipole can be recorded by MEG (Deffke et al 2007;Halgren et al 2000;Linkenkaer-Hansen et al 1998;Sams et al 1997;Swithenby et al 1998;Tanskanen et al 2005;Watanabe et al 1999a, b).…”
Section: Introductionmentioning
confidence: 91%
“…[1,4]). While the source locations in our previous study were for familiar face comparison task, preliminary results showed that this model was applicable to an alternative task, indicating task-sensitive areas [21]. In the present study we aimed at studying further the inter-task differences.…”
Section: Introductionmentioning
confidence: 93%
“…A spatio-temporal multiple dipole model contains several equivalent dipoles with fixed locations and orientations that represent active brain areas and change their activity in time domain. Previously we have reported a model including eight dipoles for the ERPs recorded at the comparison stage in a similar experiment [21]. The source locations and orientations were similar to those from that model and unchanged through all conditions, to clarify the role of certain brain areas at various steps of the task performance.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation